2009
DOI: 10.1016/j.bbmt.2009.04.016
|View full text |Cite
|
Sign up to set email alerts
|

BK Virus Infection Is Associated with Hematuria and Renal Impairment in Recipients of Allogeneic Hematopoetic Stem Cell Transplants

Abstract: BK virus (BKV) is an important pathogen and cause of nephropathy in renal transplant recipients, but its significance following hematopoetic stem cell transplantation (HSCT) is less well described. We measured blood and urine BKV in 124 allogeneic HSCT patients (67 had undergone prior HSCT [surveillance cohort]; 57 were monitored from transplant day 0 [prospective cohort]). BK viruria was manifest in 64.8% of the patients; 16.9% developed viremia. In the prospective cohort, the median time from transplantation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
61
1
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 38 publications
7
61
1
4
Order By: Relevance
“…6 Reducing immunosuppression usually is not feasible in these patients due to ongoing GVHD, and the majority of HSC transplant recipients reported to have PVAN eventually required dialysis. 4,10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Reducing immunosuppression usually is not feasible in these patients due to ongoing GVHD, and the majority of HSC transplant recipients reported to have PVAN eventually required dialysis. 4,10 …”
Section: Discussionmentioning
confidence: 99%
“…Even so, BK viremia has been implicated in kidney failure and PVAN after HSC transplantation in at least 2 studies. 10,11 In another study in HSC transplant recipients, 3 of 20 kidney biopsy specimens showed evidence of PVAN, a sign that this complication might be more prevalent than previously thought. 12 All 3 patients had BK viremia, and the pathology findings showed diffuse interstitial inflammation and tubulitis.…”
mentioning
confidence: 91%
“…O'Donnell ve ark. 'nın (13) hematopoetik kök hücre nakli yapıl-mış 124 hastada BK virüs varlığını araştırdıkları çalışmada tüm hastaların %64.8'inde BK virüri-si %16.9'unda BK viremisi saptanmıştır. Lösemi tanılı hastaların %63.4'ünde (45/71) BK virüri-si; %'18.3'ünde (13/71) BK viremisi; multiple myelom tanısı alan hastaların %33'ünde BKV DNA'sı tespit etmişlerdir.…”
Section: Discussionunclassified
“…In vitro studies examining BKPyV replication found that A771726 inhibited BKPyV replication, but that this was closely connected to the significant cytostatic effects triggered by pyrimidine depletion (139,150). There are several case reports presenting favourable outcomes in both adult (151)(152)(153)(154) and paediatric kidney transplant patients (155), but also reports where some patients experienced graft function deterioration (156,157). Of note, no difference in clearance of viremia was found between patients maintained at a high (>40 lg/mL) or low dose (<40 lg/mL) (149).…”
Section: Treatment Pyvanmentioning
confidence: 99%